Analisa Kinerja Aliran Fluida dalam Rangkaian Seri dan Paralel dengan Penambahan Tube Bundle pada Pompa Sentrifugal - Muhammad Marzuky Saleh; Edi Widodo (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2018)
Pump is a device used to move fluid from one place to another through the pipe media as a channel. The pump has 2 important components in its performance, namely: Impeller and pump house (casing). When the pump cannot meet the required capacity it can use series and parallel pump circuits to increase it. When moving the fluid to a high surface or high pressure it will have the specifications of the head and discharge. Fluid flow is a liquid that flows in a pipe. In flow there is fluid pressure and also flow type. There are 3 flow types, namely laminer, transition, turbulent. To reduce turbulence in the flow can be used Tube bundle which is a device consisting of several pipes that are tied together that are attached to a cross section in the pipe. This research was conducted in 4 testing stages, namely series circuit with additional tube bundle, series circuit without additional tube bundle, parallel circuit with additional tube bundle, parallel circuit without additional tube bundle. Each test takes fluid pressure, discharge, flow type. From the results of this study it was found that the parallel circuit pump with an additional tube bundle produces fluid pressure, discharge, flow velocity smaller than the series circuit, whereas when without additional the parallel tube pump bundle produces a fluid pressure, discharge, flow velocity greater than the circuit series, while for the flow type of this study is turbulent flow.